Wilfrid H.G. Haacke and Eliphas Eiseb. Khoekhoegowab-English / English-Khoekhoegowab Glossary / Mfdi Saogub - Snyman, J.W. (Lexikos, 2000)
The publication of the two-way Khoekhoegowab-English / English-KhoekhoegowabGlossary by Prof. Wilfrid H.G. Haacke and Pastor Eliphas Eiseb is a most welornecontribution to the lexicographical literature of Namibia. This glossary,~hich is an extract from the more extensive Khoekhoegowab Dictionary (forthcoming)by the same authors, contains more than 4 300 Khoekhoegowabentries. Apart from reviewing the glossary, the following comments also complywith Prof. Haacke's request (p. v) to supply him with "anything useful for afuture edition". The glossary has as its predecessors J. Olpp's Nama-DeutchesWorterbuch (Eberfeld, 1888), J.C. Kronlein's Wortschatz der Khoi-khoin (Berlin,1889) and F. Rust's Deutsch-Nama Worterbuch (Windhoek, 1960). Although theglossary is not solely intended for educational purposes, it is bound to have asignificant impact on the teaching and development of Khoekhoegowab inNamibia.